Marcello Mastroianni e Peter Brook - Franco Perrelli (Il castello di Elsinore, 2017)
The essay, focusing on the relationship between Marcello Mastroianni and Peter Brook (1984), also analyzes the relationship of the Italian actor with his theatrical and cinematographic vocation, in relation to the historical situations of Italian theatre.